Strategic planning and accountability of waqf management in Malaysia - Siraj, Siti Alawiah; Ismail, Yusof (2015)
Waqf is a significant institution in Islam. However, for decades the relevant authorities in Malaysia appear to give little attention on its management and development. Based on Malaysian experience, Waqf is managed by State Islamic Religious Councils (SIRCs) which are the sole trustees for waqf resources. Waqf management is governed by respective state enactments (laws). However, in recent years there has been an increasing interest in reviving waqf institution to commensurate with the pressing demands for greater accountability in public sector organizations. This study was carried out to empirically investigate the strategic planning and accountability aspects of the waqf management in Malaysia. It used a formulated questionnaire and semi-structured interviews to examine the current practices of the strategic planning function of waqf in SIRCs. The questionnaire was administered on senior officers working in thirteen SIRCs. Similarly the interviews were conducted on the senior officers of the SIRCs. The study revealed two major findings. Firstly, SIRCs used strategic planning as planning and control tool. Consequently, strategic planning is characteristically budgetary in nature and deemphasizes efficiency and effectiveness of resource utilization. Secondly, strategic planning in SIRCs is also reactionary and mainly influenced by external requirements. These practices reflect the state of the extent of accountability and effectiveness of the waqf management in Malaysia.